On the problem of school environmental education - Romanova O. V. (Actual problems of education fundamentalization)
The article deals with the problem of formation of ecological thinking of young people. The level of development of the ecological culture of society depends largely on the goals of school education, the structure and content of each subject of the natural science cycle of secondary schools.
Keywords: экологическое образование; экологическая культура; экологическое мышление; environmental education; environmental culture; environmental thinking